2013
DOI: 10.1021/jp4018458
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anchoring Process of Tethered Unsymmetrical Zn-Phthalocyanines on TiO2 Nanostructured Thin Films

Abstract: Thin nanoporous TiO 2 layers, deposited by dc reactive sputtering, have been functionalized with a novel unsymmetrical Zn(II) phthalocyanine (ZnPc-II) bearing a push−pull system, properly designed for application in dye sensitized solar cells. The anchoring process has been studied by combining visible absorption (vis), X-ray photoelectron spectroscopy (XPS), and atomic force microscopy (AFM) in order to investigate the molecular assembly during the early stage of the sensitizing process. The vis and XPS measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 53 publications
2
27
0
2
Order By: Relevance
“…From the comparison it emerges that the gig-lox layer annealed at 500 °C accommodates the largest amount of molecules, likely due to the crystallographic improvement of the surface exposed by the TiO 2 rods edges with respect to the starting material, comprising: a) the faceting of the external surfaces (see TEM in Fig. 5) and b) a likely increased reactivity of the anatase surfaces in comparison to less ordered surfaces342563. Note that a value of ∼1 × 10 20 molecules/cm 3 is consistent with a complete pore filling as calculated by taking into account the full volume of the pores and the N-719 size (the volume occupied by each molecule was ∼3.8 nm 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the comparison it emerges that the gig-lox layer annealed at 500 °C accommodates the largest amount of molecules, likely due to the crystallographic improvement of the surface exposed by the TiO 2 rods edges with respect to the starting material, comprising: a) the faceting of the external surfaces (see TEM in Fig. 5) and b) a likely increased reactivity of the anatase surfaces in comparison to less ordered surfaces342563. Note that a value of ∼1 × 10 20 molecules/cm 3 is consistent with a complete pore filling as calculated by taking into account the full volume of the pores and the N-719 size (the volume occupied by each molecule was ∼3.8 nm 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, hybrid solar cells replacing the dye with hybrid Perovskites (PSC) materials1819202122 as sensitizer allowed getting efficiency values as high as 22.1% using advanced mixed perovskites2324. In the standard scheme of the photo-anode of a DSC4 or PSC18, a mesoporous thin film of nanosized TiO 2 crystals is deposited on a Transparent Conductive Oxide (TCO), annealed for grains sintering and anatase crystallization (typically at 500 °C), and subsequently imbued with a photoactive dye2526272829 or infiltrated with perovskite30. In both cases, mesoporous TiO 2 in the anatase polymorphism has emerged as the most appropriate choice for cell scaffold15212331.…”
mentioning
confidence: 99%
“…Another related example, in which the carboxylic acid group is connected to the Pc core through a phenylethynyl linker, was reported by Zanotti et al43 The role of the concentration of this ZnPc in the anchoring process was studied by UV/Vis, XPS and AFM, revealing strong interaction between the Pc and the TiO 2 surface at low molecular surface density 44. In addition, even though DFT calculations showed that the introduction of a phenylethynyl unit provides considerable electronic coupling between the dye's LUMO and the TiO 2 3d orbital, the power conversion efficiency remained lower than 1 % 44…”
Section: Phthalocyanines In Dsscsmentioning
confidence: 95%
“…Silanization using a linker with a -Si(OR) 3 end group was used to anchor a Zn porphyrin on a TiO 2 surface [465]. In a study by Pellegrino et al, a ZnPc derivative with a benzoic acid side group was used for covalent tethering on TiO 2 films [108,466]. The electron transfer dynamics of a porphyrin with the benzoic acid side group anchored on a ZnO surface was subject of a time-dependent DFT study [467].…”
Section: Tetrapyridylporphyrinsmentioning
confidence: 99%